Positive affect, intuition, and feelings of meaning. [article]. - Hicks, Joshua A.
Subjective rationally, or the feeling of meaning, was identified by William James (1893) as a central aspect of the non-sensory fringe of consciousness. Three studies examined the interaction of positive Affect (PA) and individual differences in intuitive information processing in predicting feelings of meaning for various stimuli and life events. In study 1 (N=352), PA and intuition interacted to predict understanding for ambiguous quotes and abstract artwork. In study 2 (N=211), similar interactions were found for feelings of meaning for fans after their football team lost a conference championship game and for individuals not directly affected by Hurricane Katrina in events surrounding the hurricane. In study 3 (N=41), induced PA interacted with individual differences in intuition in predicting accuracy for coherence judgements for loosely related linguistic triads . Intuitive individuals in the positive mood condition recognized coherent triads more accurately than did other participants. Results are discussed in terms of the role of individual differences in intuitive information processing in the relationship of PA to cognition. -- (from the author)